Review of Hawaiian Elmomyza species (Diptera, Drosophilidae, Scaptomyza). I. The cyrtandrae, exigua, and obscuricornis species groups, with the descriptions of nine new species - Rampasso, Augusto Santos; O'grady, Patrick Michael (Zootaxa, 2025)
The subgenus Elmomyza, with 86 Hawaiian endemic species of the 274 described species of Scaptomyza, is the most diverse lineage in Scaptomyza. Here, we describe nine new species of Elmomyza (S. hiiakae, S. hinae, S. kamohoalii, S. kanaloai, S. kanei, S. kui, S. lonoi, S. mauii, S. peleae), bringing the total species in this subgenus to 95. We also redescribe S. exigua, including high-resolution images of the male terminalia, and update the published identification key. We expand the collection records for the Scaptomyza cyrtandrae species group and use morphology to erect two new species groups, the Scaptomyza exigua and obscuricornis species groups. Each of these groups is further divided into subgroups. In total, 28 (~30%) Elmomyza species are now placed into species groups. This is the first step into revising the subgenus Elmomyza, which still contains dozens of new species that are known, yet remain undescribed.